Time to Rethink the Current Paradigm for Assessing Kidney Function in Drug Development and Beyond. Issue 5 (18th December 2021) - Sharma, Ashish; Sahasrabudhe, Vaishali; Musib, Luna; Zhang, Steven; Younis, Islam; Kanodia, Jitendra
Abstract : Chronic kidney disease (CKD) is an important health issue that affects ~ 9.1% of the world adult population. Serum creatinine is the most commonly used biomarker for assessing kidney function and is utilized in different equations for estimating creatinine clearance or glomerular filtration rate (GFR). The Cockcroft–Gault formula for adults and "original" Schwartz formula for children have been the most commonly used equations for estimating kidney function during the last 3–4 decades. Introduction of standardized serum creatinine bioanalytical methodology has reduced interlaboratory variability but is not intended to be used with Cockcroft–Gault or original Schwartz equations. More accurate equations (for instance, Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) for adults and bedside Schwartz or Chronic Kidney Disease in Children Schwartz equation for children) based on standardized serum creatinine values (and another biomarker—cystatin C) have been introduced and validated in recent years. Recently, the CKD‐EPI equation refitted without a race variable was introduced. Clinical practice guidance in nephrology advocates a shift to these equations for managing health care of patients with CKD. The guidance also recommends use of albuminuria in addition to GFR for CKD diagnosis and management. Significant research with large data sets would be necessary to evaluate whether this paradigm would also be valuable in drug dose adjustments. This article attempts to highlight some important advancements in the field from a clinical pharmacology perspective and is a call to action to industry, regulators, and academia to rethink the current paradigm for assessing kidney function to enable dose recommendation in patients with CKD.